2020
DOI: 10.1021/acs.nanolett.0c03692
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Surface Acoustic Waves and Spin Waves: The Role of Anisotropy and Spatial Profiles of the Modes

Abstract: The interaction between different types of wave excitation in hybrid systems is usually anisotropic. Magnetoelastic coupling between surface acoustic waves and spin waves strongly depends on the direction of the external magnetic field. However, in the present study we observe that even if the orientation of the field is supportive for the coupling, the magnetoelastic interaction can be significantly reduced for surface acoustic waves with a particular profile in the direction normal to the surface at distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 32 publications
1
36
0
3
Order By: Relevance
“…[ 9 , 10 ] Other studies of coupling between spin waves and SAW have also been reported. [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ] Here, we have harnessed this interaction to implement a novel antenna whose gain and radiation efficiency exceed the theoretical limits by two orders of magnitude or more.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9 , 10 ] Other studies of coupling between spin waves and SAW have also been reported. [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ] Here, we have harnessed this interaction to implement a novel antenna whose gain and radiation efficiency exceed the theoretical limits by two orders of magnitude or more.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the in-plane anisotropy of SWs dispersion has to be taken into account for the design of magnonic devices where SAW are exploited to control or generate SWs. Interestingly, some recent articles put into evidence the important role played by a nonzero wavevector [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Babu et al studied the SAW-SW coupling by Brillouin Light Scattering (BLS) in a wide kvalues range [14]. They showed that in order to obtain an appreciable coupling between SWs and SAWs, the SAW profile within the magnetostrictive layer is also of importance, [14] in addition to the anisotropy of the magnetoelastic interaction with respect to the orientation of the magnetic field [10].…”
Section: Introductionmentioning
confidence: 99%
“…The study of magnon-phonon interactions in highquality magnets has a long history [14][15][16][17][18][19][20][21]. The arrival of crystal growth techniques, strongly improved microwave technology, and discovery of new phenomena such as the spin Seebeck effect, led to a revival of the subject in the past few years, with emphasis on ultrathin films and heterostructures [4,6,[22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%